1987
DOI: 10.1128/aac.31.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-infusion ampicillin therapy of enterococcal endocarditis in rats

Abstract: Intermittent administration of ampicillin alone has resulted in high failure rates in previously described animal models of enterococcal endocarditis. We developed a rat model of enterococcal endocarditis which permits comparison of continuous intravenous infusion of ampicillin with intramuscular therapy. Continuous low-dose ampicillin infusion (450 mg/kg [body weight] per day) was compared with the same dose given intramuscularly in three divided doses and with high-dose infusion (4.5 g/kg per day) of the dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 24 publications
2
56
2
Order By: Relevance
“…The superior effectiveness of continuous infusion over intermittent infusion has been demonstrated for ␤-lactams in animal studies (2,8,25,26); however, clinical data comparing continuous and intermittent infusions are limited and consist primarily of data from small studies and case reports (1,3,6,9,10,11,19,22,28). In most of these studies, similar clinical and microbiological outcomes have been observed for the two administration techniques, but none of the studies have had sufficient power to conclude noninferiority.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The superior effectiveness of continuous infusion over intermittent infusion has been demonstrated for ␤-lactams in animal studies (2,8,25,26); however, clinical data comparing continuous and intermittent infusions are limited and consist primarily of data from small studies and case reports (1,3,6,9,10,11,19,22,28). In most of these studies, similar clinical and microbiological outcomes have been observed for the two administration techniques, but none of the studies have had sufficient power to conclude noninferiority.…”
mentioning
confidence: 86%
“…Although the concept of continuous infusion is supported by ␤-lactam pharmacodynamics (8,27), suggesting that maximization of the fT Ͼ MIC should be a critical factor for a positive outcome, clinical studies supporting this are limited. The majority of supporting data have been derived from either in vitro or animal models of infection, which demonstrated equivalent or improved end points with continuous infusion (2,25,26), or from small case reports, retrospective studies, or prospective observational trials (1,9,10,11,14,20,22,28). In one randomized, comparative trial of 100 febrile neutropenic patients, intermittent carbenicillin infusion plus continuous cefamandole infusion achieved a greater effectiveness than intermittent carbenicillin infusion plus intermittent cefamandole infusion in the subgroup of patients with agranulocytosis (absolute neutrophil count, Ͻ100/mm 3 ) (4).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is not known whether an MBC, or for that matter any in vitro or animal model criteria, can predict clinical cures. One group reported better success in a rat model of endocarditis by using continuousinfusion ampicillin versus intermittent ampicillin for a strain of enterococcus highly resistant to gentamicin (205). However, that strain also showed a 103-CFU/ml decrease from a 107-CFU/ml inoculum in time-kill curves, using 5, 10, and 250 ,ug of ampicillin per ml, and the authors comment that other strains may display more tolerance to ampicillin.…”
Section: Management Of Enterococcal Infections Therapymentioning
confidence: 99%
“…To cast further doubt on the bacteriologic identification, all of the enterococci were said to be susceptible to cephalothin and one to clindamycin, unusual properties for enterococci (79). In vitro, vancomycin is usually not bactericidal, and it does no better in animal models than penicillin alone (27,99,104,135,205,217). Among other agents that have been evaluated, ciprofloxacin was less effective than procaine penicillin in controlling enterococcal endocarditis (75,104,195).…”
Section: Management Of Enterococcal Infections Therapymentioning
confidence: 99%
“…Most of these conclusions regarding the relation between the pharmacodynamics of antibiotics and optimal dosage have been verified in experimental bacterial endocarditis (9,36,39,50,51,55).…”
Section: Pharmacokinetics Of Antibiotic Penetration Into Fibrin Vegetmentioning
confidence: 99%